Business solutions on demand transform the business to deliver real customer value - Cerasale, Mark Vincent 1969-; Stone, Merlin 1948-.; Gale Group (London Kogan Page, 2004)
Based partly on IBM's own transformation, and partly on the transformations that IBM has helped its clients to achieve, this groundbreaking book shows how companies can increase sales and improve margins by introducing a range of solutions. Drawing on IBM's extensive experience of working with clients all over the world, the book is packed with examples from a diverse range of industries.
Business strategy and transformation -- Transformation in food retailing -- The low-cost business model -- The solutions business model -- Transformation in the information technology -- Industry -- Industries transforming -- Business innovation -- The business innovator -- Solution creation and delivery -- The customer relationship manager -- Solution marketing -- The industry marketing manager -- Knowledge management -- The knowledge manager -- Business design -- Change management.
Electronic reproduction.
Keywords: Business planning; Strategic planning; Electronic books